Forest governance and rural-architecture practices: A comparative study of Baduy (Indonesia) and Temiar (Malaysia) - Salmina Wati Ginting; Isnen Fitri; Norhazlan Haron; Seng Boon Lim (Talenta Publisher, 2026)
Forests are central to the material, ecological, and cultural foundations of rural life in Southeast Asia. In Indonesia and Malaysia, the availability of timber and bamboo is shaped by customary norms and national forest governance. It continues to influence construction practices, settlement form, and the durability of rural architecture. Nevertheless, research rarely examines how forest management regimes directly affect material flows from forests to dwellings. This article addresses this gap by comparing two forest-dependent communities: the Baduy of Banten, Indonesia, and the Temiar Orang Asli of Peninsular Malaysia. Using a mixed documentary and remote-analysis approach, the study synthesises peer-reviewed literature (2018–2024), ethnographic documentation, and photographic archives to examine how customary and state governance systems regulate timber and bamboo extraction, species selection, and settlement morphology. The findings show that the Baduy maintain a highly restrictive customary forest-management regime that conserves forest structure, ensures long-term availability of hardwood species, and sustains an ecologically continuous timber-bamboo architectural tradition. In contrast, the Temiar operate within hybrid governance shaped by state forest policies, logging concessions, and customary ethics, resulting in more variable timber access and adaptive construction strategies. Across both cases, forest governance emerges as a critical determinant of material choice, spatial adaptation, and the technical performance of rural buildings. The study argues that timber architecture in rural Southeast Asia cannot be separated from the forest systems that regulate and supply its materials. These insights highlight the need for forestry policies that recognise the architectural and spatial implications of forest management and support community-based, ecologically rooted building cultures